Defining gay-friendly city as a space of resistance for Indonesian gays in Paris and Jakarta - Wisnu Adihartono (Universitas Trunojoyo Madura, 2021)
Migration is associated with the search for a more permissive environment. By linking Paris as a place of attachment, the author sees that Paris in this case can be indicated as the “home” for Indonesian gays. The feeling of “full gay” is a feeling that they never get when they stay in Indonesia. That is why many Indonesian gays decide to move out of Indonesia in any way regardless of the difficulties they face in the destination country. This paper answer two questions: what do we understand by “Gay-friendly city”? And if we talk about Jakarta, “can Jakarta be categorized as a gay-friendly city”? The author interviewed eight Indonesian gays directly in Paris with the naturalistic paradigm and analyzed with the qualitative research, and what will be found in this paper is the narrative of the eight informants. It can be said that the Indonesian gays who have migrated to Paris do not feel that their lives have been wasted. They do diaspora by going to gay bars and participating in gay pride parades. What they feel is a feeling of freedom to be able to channel their gender and sexual expression, and they found that Paris as a gay-friendly city is a kind of space of resistance.